2011
DOI: 10.1111/j.1365-2621.2011.02762.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of dried pasta enriched with buckwheat flour

Abstract: The addition of pseudocereal flours to semolina is becoming more and more popular to improve the nutritional quality of the resultant pasta. The aim of this study was the evaluation of several properties of commercial pasta made from a mixture of buckwheat flour and durum wheat semolina. The characterisation of products, belonging to different producers, focused on the evaluation of chemical and physical properties, such as water uptake and mechanical properties before and after cooking and surface characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The gluten network should be more developed by sheeting than by extrusion (Pagani et al, 1989) (Figure 9.6). In a recent work, Marti et al (2011a) reported low breaking strength for dry pasta prepared from composite flours and by sheeting, usually responsible for a more porous structure, and related to high cooking losses during cooking. On the other hand, the sheeting process by rolls allows the protein to align in a continuous network whose goodness strongly depends on protein quantity and quality (Figure 9.6).…”
Section: Factors Influencing the Textural Properties Of Pastamentioning
confidence: 99%
See 1 more Smart Citation
“…The gluten network should be more developed by sheeting than by extrusion (Pagani et al, 1989) (Figure 9.6). In a recent work, Marti et al (2011a) reported low breaking strength for dry pasta prepared from composite flours and by sheeting, usually responsible for a more porous structure, and related to high cooking losses during cooking. On the other hand, the sheeting process by rolls allows the protein to align in a continuous network whose goodness strongly depends on protein quantity and quality (Figure 9.6).…”
Section: Factors Influencing the Textural Properties Of Pastamentioning
confidence: 99%
“…In the extrusion process commonly used for semolina pasta production, the dough is submitted to significant shear stresses, which can weaken the poor quality protein structure (Pagani et al, 1989), but, at the same time, to pressure (9-10 MPa), responsible for giving the product a high compactness, and allowing it to withstand cooking (Petitot et al, 2009b). On the other hand, the roll-sheeting step that allowed a better alignment of the gluten strands (Pagani et al, 1989), accounting for low adhesiveness during cooking (Marti et al, 2011a). In a recent work, Marti et al (2011a) reported low breaking strength for dry pasta prepared from composite flours and by sheeting, usually responsible for a more porous structure, and related to high cooking losses during cooking.…”
Section: Factors Influencing the Textural Properties Of Pastamentioning
confidence: 99%
“…It has been reported that no gluten aggregation was found in IWG (Becker et al 1991), indicating that IWG flour is not suitable for preparing glutenbased foods such as bread and pasta. In regard to starch, changes in viscosity of cereal flours or starches during heating and cooling provide information on molecular changes promoted by processing conditions or ingredient interactions (Marti et al 2011). More information from a molecular standpoint (starch and protein) on this crop is required in view of a possible application of IWG flour cereal-based products.…”
mentioning
confidence: 99%
“…categories #4 and 6) had similar a* and b* values ( P > 0.05). High a* values were observed for those GF pasta samples containing buckwheat flour and/or whole rice flour as main ingredient (categories #2, 7, 10, 5, respectively) as previously observed by other authors (Marti et al ., ). Also, L* values of GF pasta samples were all higher than 60, with the exception pasta samples made from corn and potato starches, lupine flour (#3) and whole rice flour (#7).…”
Section: Resultsmentioning
confidence: 98%